Gendered Linguistic Analysis of Jane Austen's 'Emma': Unveiling Feminist Perspectives at the Word Level - Br Pane, Khairina Juliana; Lubis, Syahron; Rangkuti, Rahmadsyah; Br Perangin – Angin, Alemina (EduLite: Journal of English Education, Literature and Culture, 2024)
This research aims to analyze the stylistic and linguistic selection in representing women in Jane Austen’s novel entitled Emma by emphasizing the gender specific words presented in the novel and discover the gender specific theme exposed in the novel. This research conducts a qualitative analysis to explore the stylistic and linguistic choices employed in depicting women in Jane Austen's novel, "Emma." Focusing on gender-specific words within the text, the study aims to uncover the novel's thematic presentation of gender. Utilizing Sara Mills' feminist stylistics theory as a framework, the linguistic structure at the word level is examined to portray female characters and assess its societal impact. By decoding Austen's linguistic strategies, this analysis provides a critical lens for examining gender representation within the novel and its broader societal implications. The study contributes to literary and linguistic scholarship, enhancing the understanding of Austen's narrative techniques and shedding light on societal perceptions of gender.